Single Percutaneous Tract Combined with Flexible Nephroscopy in the Management of Kidney Stones 2-4 cm: Better Options of Treatment Protocols - Zhang, Xiaobo; Gu, Jie; Chen, Xiong; Dai, Yuanqing; Chen, Mingquan; Hu, Sheng; Liu, Zhenyu; Li, Dongjie (Urology Journal, 2020)
Purpose: To investigate the safety and efficacy of single percutaneous tract combined with flexible nephroscopy in the Management of 2-4 cm renal calculi. Materials and Methods: We retrospectively analysed the treatment data of patients with 2-4 cm renal calculi from June 2010 to June 2017. The data included 217 cases of percutaneous nephrolithotomy (PNL), 441 cases of retrograde intrarenal surgery (RIRS) and 217 cases of single-access percutaneous nephrolithotomy combined with flexible nephroscopy (PNCFN). The collected data were analyzed. Results: A total of 875 cases were studied, with an average age of 42.35 ± 10.29 years. Group PNCFN showed the highest stone-free rates (SFRs)(73.7 vs 66.7 vs 80.2, P = .00), best patient satisfaction (89.84 vs 87.23 vs 92.29, P = .00). The length of stay was shorter in the RIRS group relative to the other two groups (5.22 vs 5.65 vs 3.72, P = .00). Haemoglobin decrease (> 10 g/L) was higher in group PNL than that in group RIRS and group PNCFN (P = .012). Hospitalization fees (RMB) were Increased in group PNCFN compared with that in group PNL and group RIRS (34563.45 vs 21334.69 vs 33343.16, P = .000). Treatment protocols of PNL decreased from 17.51% to 9.22%, those for RIRS from 5.22% to 17.69%, peaking at 2012, PNCFN from 8.29% to 15.67% showed a rapid growth trend. Conclusion: The percutaneous nephrolithotomy combined with flexible nephroscopy treatment on renal calculi of 2-4 cm was associated with higher stone-free rates and better patient satisfaction than RIRS and PNL.